4B.01: CONTRASTING INFLUENCES OF RENAL FUNCTION ON BLOOD PRESSURE AND HBA1C REDUCTIONS WITH EMPAGLIFLOZIN IN PATIENTS WITH TYPE 2 DIABETES AND HYPERTENSION. (June 2015) - Cherney, D.; Cooper, M.; Tikkanen, I.; Crowe, S.; Johansen, O.E.; Lund, S.S.; Woerle, H.J.; Broedl, U.C.; Hach, T.
Abstract : Objective: To determine if impaired renal function attenuates antihypertensive effects of empagliflozin. Design and method: In a Phase III randomised placebo-controlled trial (EMPA-REG BP TM ), patients with type 2 diabetes and hypertension (defined as mean seated office systolic blood pressure [SBP] 130–159 mmHg and diastolic BP 80–99 mmHg at screening) received empagliflozin 10 mg, empagliflozin 25 mg or placebo for 12 weeks (mean [SD] age 60.2 [9.0] years, HbA1c 7.90 [0.74] %, 24-hour SBP 131.4 [12.3] mmHg). We assessed changes from baseline in mean ambulatory 24-hour SBP and HbA1c in subgroups by baseline eGFR (MDRD equation). Results: In patients with normal renal function, stage 2 or 3 chronic kidney disease (CKD; eGFR >=90 [n = 261], 60 to <90 [n = 516], 30 to <60 [n = 45] ml/min/1.73m 2, respectively), empagliflozin significantly reduced HbA1c and mean 24-hour SBP versus placebo. As expected, placebo-corrected HbA1c reductions with empagliflozin appeared to decrease with decreasing eGFR. Differences versus placebo in changes from baseline in mean 24-hour SBP were −3.8 (−6.3, −1.4) and −3.4 (−5.7, −1.1) mmHg with empagliflozin 10 mg and 25 mg, respectively, in patients with normal renal function, −2.7 (−4.4, −1.1) and −4.5 (−6.2, −2.8) mmHg, respectively, in patients with stage 2 CKD, and −11.0 (−17.4, −4.6) and −6.8 (−12.6, −1.0) mmHg, respectively, in patients with stage 3 CKD (all p < 0.05). Conclusions: Unlike HbA1c, reductions in mean 24-hour SBP with empagliflozin in patients with type 2 diabetes and hypertension appear to be greater in patients with lower eGFR, indicating that SBP modulation with empagliflozin may involve pathways other than urinary glucose excretion.